Risk Factors for Readmission following Anterior Cruciate Ligament Reconstruction - Best, Matthew J.; Harris, Andrew B.; Marrache, Majd; Martin, Scott D.; Rue, John-Paul H.; Wilckens, John H. (The Journal of Knee Surgery, 2021)
The purpose of this study is to identify risk factors for readmission after anterior cruciate ligament (ACL) reconstruction and to determine costs associated with readmission. Using a private insurance claims' database, we identified patients who underwent ACL reconstruction from 2010 to 2015 using the International Classification of Diseases, Version 9 (ICD-9) and Current Procedural Terminology (CPT) codes. Univariate analysis was performed on demographic data, surgical characteristics, and comorbidities. Variables with p < 0.10 were added to a multivariate logistic regression model which was created to identify independent risk factors for all-cause readmission within 90 days postoperatively. Significance was considered at p < 0.05. Overall, 90,263 patients were included (average age: 29 ± 13 years, 44% female), and 1,066 (1.2%) of patients had a hospital readmission within 90 days following surgery. Risk factors for hospital readmission included cerebrovascular disease (odds ratio [OR] = 3.4, 95% confidence interval [CI]: 1.9, 6.2), diabetes mellitus (OR = 2.6, 95% CI: 1.9, 3.5), concomitant medial collateral ligament (MCL) or lateral collateral ligament (LCL) reconstruction (OR = 2.5, 95% CI: 1.9, 3.3), concomitant posterior cruciate ligament (PCL) reconstruction (OR = 2.2, 95% CI: 1.4, 3.3), age between 44 and 65 years (OR = 2.1, 95% CI: 1.6, 2.9), and depression (OR = 1.88, 95% CI: 1.49, 2.38, p < 0.001). Female sex was associated with decreased odds of 90-day hospital readmission (OR = 0.8, 95% CI: 0.7, 0.9). Each hospital readmission accounted for an estimated $17,841 (95% CI: $17,173, 18,509) in gross health care payments, and patients with readmissions had substantially higher 1-year cumulative health care costs. Readmission after ACL reconstruction was 1.2%. The strongest risk factors for 90-day readmission include cerebrovascular disease, diabetes mellitus, concomitant MCL/LCL reconstruction, concomitant PCL reconstruction, and age between 44 and 65 years. Readmission was associated with substantial health care costs.
Keywords: anterior cruciate ligament; ACL reconstruction; readmission; cost; risk factors